SARS-CoV-2 assessment in an outpatient dialysis facility of a single center in Brazil - Gorayeb-Polacchini,Fernanda Salomão (2021)
ABSTRACT Background: The reported incidence and fatality rates of SARS-CoV-2 infection in patients receiving maintenance dialysis are higher than those of the general population. Objective: This study sought to characterize the clinical characteristics and outcomes following COVID-19 infection in this population in a single center in Brazil. Methods: Out of 497 dialysis patients evaluated between March 1st, 2020 and February 1st, 2021, those presenting symptoms or history of close contact with COVID-19 patients were tested. Disease severity was categorized as mild, moderate, or severe. Results: Out of the 497 patients, 8.8% tested positive for COVID-19. These patients were predominantly male (59%), mean age 57.5 ± 17. Hospitalization was required for 45.4% of patients and 15.9% received mechanical ventilation. Symptoms such as fever, cough, dyspnea and asthenia were more frequent in the severe group. Neutrophil to lymphocyte ratio, C- reactive protein, glutamic oxalacetic transaminase and lactic dehydrogenase were significantly higher in the severe group, while hemoglobin and lymphocyte counts were significantly lower. Chest CT >50% of ground glass lesions was the risk factor associated with severe disease and need for hospitalization. The incidence of a thromboembolic event was of 22.7% in this population. The incidence, mortality, and case fatality rates were 954.4/10,000 patients, 151.8/10,000 patients, and 15.9%, respectively. Conclusions: The incidence, mortality and case fatality rates in our cohort were significantly higher than those reported for the general population. To institute appropriate control measures and early vaccination in dialysis facilities is imperative to prevent the spread of COVID-19 infection.